과업 계획이 EFL 학습자의 쓰기 수행에 미치는 영향 - 주미진(Joo, Mi-jin) (영어교육연구, 2021)
This study aims to investigate the effects of three types of planning conditions (no planning, pretask planning, and on-line planning) on fluency, complexity, and accuracy in L2 writing. Each of 60 Korean university students performed their assigned tasks under the three different types of planning conditions. The results show that; first, pre-task and on-line planning resulted in improving complexity, fluency, and accuracy compared to no planning. Accuracy was significantly improved only when in on-line planning; secondly, complexity had strong relationship with fluency in all types of planning conditions; finally, accuracy was negatively correlated with complexity and fluency in pre-task planning while not related to those in on-line planning. (108 words) KCI Citation Count: 0